Information and communication technology workforce employability in Malaysia - Suhaimi, Mohd Adam; Hassan, Muhammad Rabiul; Hussin, Husnayati; Shah, Asadullah (Emerald, 2012)
Purpose – The purposes of the study are to understand ICT workforce employability in Malaysia, to identify the causes that influence the growth of skill gaps in the ICT workforce, and to determine ways to reduce these gaps. Design/methodology/approach – The methodology of the study comprised project reports and a literature review. Findings – The findings show that not only Malaysia but also Australia and India are facing the challenges of demand-supply gap as regards a quality ICT-related workforce. The study also indicates that these countries do have similar obstacles and issues of sufficiently trained and experienced ICT graduates. Practical implications – This study suggests that in the light of the skills demanded by industries and organizations, ICT workers could be trained through an updated course curriculum in line with the needs of industry. Originality/value – The employability of the workforce in general has been discussed in many papers. This paper specifically discusses employability issues of the information and communication technology (ICT) workforce, and provides values to ICT educators and employers, as well as to potential ICT graduates. Keywords Information technology, Educational institutions, Training, Curriculum, Skills, Malaysia, Labour specialization Paper type Research paper